Ovalbumin-mediated synthesis and simultaneous functionalization of graphene with increased protein stability - Ullah, Riaz; Khan, Shadab Ali; Aladresi, Aref Ali Mohammed; Alharbi, Sulaiman Ali; Chinnathambi, Arunachalam (Green Chemistry Letters and Reviews, 2020)
In this article, we have shown an easy, one-step, protein-directed approach for the synthesis of water-soluble and functional graphene using ovalbumin. The obtained ovalbumin functionalized graphene was characterized by UV-visible spectroscopy, X-ray diffraction, Raman spectroscopy, and Fourier transform infrared spectroscopy. Atomic force microscopy was used to check the attachment/functionalization of ovalbumin on grapheme sheets. It was shown that the functionalization of ovalbumin on grapheme sheets makes the protein more thermally stable compare to free ovalbumin, which has been shown by using sodium dodecyl sulfate polyacrylamide gel electrophoresis.
Keywords: Atomic force microscopy; graphene; graphene oxide; Ovalbumin; SDS-PAGE; thermal degradation

SNP discovery and structural insights into OeFAD2 unravelling high oleic/linoleic ratio in olive oil - Ben Ayed, Rayda; Moreau, Fabienne; Ben Hlima, Hajer; Rebai, Ahmed; Ercisli, Sezai; Kadoo, Narendra; Hanana, Mohsen; Assouguem, Amine; Ullah, Riaz; Ali, Essam A. (Computational and Structural Biotechnology Journal, 2022)
Fatty Acid Desaturase 2 (FAD2), a key enzyme in the fatty acid biosynthesis pathway, is involved in the desaturation and conversion of oleic acid to linoleic acid. Therefore, it plays a crucial role in oleic/linoleic acid ratio and the quality of olive oil. DNA sequencing of 19 FAD2 genes from a set of olive oil varieties revealed several single-nucleotide polymorphisms (SNPs) and highlighted associations between some of the SNPs and saturated fatty acids contents. This was further confirmed by SNP-interaction and machine learning approach. Haplotype diversity analysis led to the discovery of three highly polymorphic SNPs and four haplotypes harboring differential oleic/linoleic acid ratios. Moreover, a combination of molecular modeling and docking experiments allowed a deeper and better understanding of the structure-function relationship of the FAD2 enzyme. Sequence patterns and variations involved in the regulation of the FAD2 activity were also identified. Furthermore, S82C and H213N substitutions in OeFAD2 make the Oueslati variety more interesting in terms of fatty acid profile and oleic acid level. (C) 2022 The Authors. Published by Elsevier B.V. on behalf of Research Network of Computational and Structural Biotechnology.
Keywords: docking; Fatty acid desaturase; Haplotype; machine learning; Oleic/linoleic acid ratio; Protein structure